Insulin Induces Internalization of the Plasma Membrane 5-Hydroxytryptamine2A (5-HT2A) Receptor in the Isolated Human Endothelium-Denuded Saphenous Vein via the Phosphatidylinositol 3-Kinase Pathway - Tasuku Kanai; Masachika Kuwabara; Naoko Tanaka-Totoribe; Eisaku Nakamura; Yasuko Matsuo; Shuji Gamoh; Akito Suzuki; Yujiro Asada; Hiroaki Hisa; Ryuichi Yamamoto (Elsevier, 2012)
The aim of this study was to investigate the relaxant effect of insulin on the 5-hydroxytryptamine (5-HT)-induced constriction of the human endothelium-denuded saphenous vein (SV) and its signal transduction pathway. During the 5-HT-induced sustained constriction of vessels, insulin induced vasorelaxation in a concentration-dependent manner. This insulin-induced vasorelaxation was partially attenuated by L-NAME, a nitric oxide synthase (NOS) inhibitor, and was abolished by wortmannin, a phosphatidylinositol 3-kinase (PI3-K) inhibitor. Insulin increased the Ser473 phosphorylation of Akt. Endothelial NOS and inducible NOS protein expressions were observed in SV smooth muscle when insulin induced relaxation of SV vessels preconstricted with 5-HT. Although insulin did not affect the total protein level of 5-HT2A receptors, it decreased the particulate protein level and reciprocally increased the soluble protein level of 5-HT2A receptors in a concentration-dependent manner. These results demonstrate that insulin can induce the internalization of 5-HT2A receptors from the plasma membrane to the cytoplasm. The insulin-induced internalization of 5-HT2A receptors was abolished by wortmannin but was not affected by L-NAME. These results suggest that the relaxant effect of insulin on 5-HT-induced vasoconstriction is mediated in part by the internalization of plasma membrane 5-HT2A receptors and the production of nitric oxide via the PI3-K/Akt pathway. Keywords:: insulin-induced vasorelaxation, saphenous vein (SV), internalization of 5-HT2A receptor, diabetes mellitus (DM), nitric oxide (NO)